2009
DOI: 10.1007/s10517-009-0614-z
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Antioxidant Enzymes in the Wound in Patients with Deep Burns

Abstract: Analysis of wound discharge in children with deep burns over 3 weeks after the injury revealed gradual increase in catalase activity. The increase in activities of myeloperoxidase, glutathione-S-transferase, and catalase was maximum in patients with the most severe burns. Local complications were observed during the period of maximum myeloperoxidase activity, while the beginning of epithelialization was associated with its reduction. Analysis of wound impressions confirms long-term persistence of neutrophils i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Vacuum, drainage, or other external devices were used in 124 of the 280 (44%) studies and thus were the most frequently used methods of sample collection 22–27,29–146 ; the vast majority of sample collections using this method (75%, 103/138), were from surgical wounds (Figure 2B). Three other frequently used methods were extraction from absorbent material (31%, 86/280),…”
Section: Resultsmentioning
confidence: 99%
“…Vacuum, drainage, or other external devices were used in 124 of the 280 (44%) studies and thus were the most frequently used methods of sample collection 22–27,29–146 ; the vast majority of sample collections using this method (75%, 103/138), were from surgical wounds (Figure 2B). Three other frequently used methods were extraction from absorbent material (31%, 86/280),…”
Section: Resultsmentioning
confidence: 99%
“…This cytokine is a potent chemoattractant and stimulator of neutrophils [6]. Our previous studies showed that intact neutrophils are present in the wound of burn patients even 3 weeks after injury [2]. Surgical cleaning of the burn wound and skin autografting can accelerate wound healing and prevent secondary necrosis [8].…”
mentioning
confidence: 99%
“…Blood test: The pathogenesis of burn disease is strongly influenced by decreased antioxidant activity (AOA). In burns, AOA levels decrease significantly in blood serum and membranes of erythrocytes, providing indirect confirmation of a decrease in endogenous antioxidant levels [31,32]. Based on Table 5, burns (control group (II)) showed a decrease in SAA.…”
Section: The Experiments Modeled On a Thermal Burnmentioning
confidence: 99%